Managing Skin Cancer - Stockfleth, Eggert; Rosen, Ted; Schumaak, Steven (Springer Berlin Heidelberg : Imprint: Springer, 2010)
Skin cancer is the most common malignant neoplasm and its incidence is rising worldwide. The epidemic increase in such tumors calls for efficient management by the application of appropriate guidelines for therapy and prevention. Clinicians managing patients with skin cancer need to keep up to date with the latest advances, allowing them to provide optimal treatment. This practical guide offers the reader a comprehensive overview of the options for the diagnosis, treatment, and prevention of cutaneous cancer. It covers all common skin cancers, as well as some less frequent and precancerous lesions, including: malignant melanoma basal cell carcinoma actinic keratosis Kaposi´s sarcoma and Merkel cell carcinoma. Employing an "evidence-based medicine" approach, this truly international work presents a well-illustrated text in a reader-friendly format with step-by-step guidelines and visual flowcharts. Dermatologists, oncologists, and all other interested physicians will find this book an extraordinarily valuable resource for the clinical management of cutaneous cancer in their daily practice.